IMPROVING STUDENTS’ READING COMPREHENSION IN ANALYTICAL EXPOSITION TEXT USING STUDENT TEAM ACHIEVEMENT DIVISION (STAD) - Zaki Munibi, Ahmad (Jurnal Locus Penelitian dan Pengabdian, 2023)
The problem with this research is the students found difficulties in reading comprehension, especially in finding the main idea of a text. The students also lack the motivation to read the text in English. Those difficulties made the students cannot fully understand the text they read. The research aims to improve students’ reading comprehension in analytical exposition text using Student Team Achievement Division (STAD). The subjects of this study were 36 students in eleventh grade at SMAN 103 Jakarta. This research only consisted of one cycle that consist of two meetings. Each cycle consists of planning, acting, observing, and reflecting. The data collecting technique used in this research was test, observation, and questionnaire. The result showed that there are improvements in the average score of the students. The score in the pre-test was 70.5 improved to 84.2 in the post-test. Using Student Team Achievement Division (STAD) also made students motivated and teamwork improved along with their individual skills. The questionnaire also showed that the students responded positively to Student Team Achievement Division (STAD), and it showed from the questionnaire result that 58% of students gave positive feedback. The result of this research indicates that the use of the Student Team Achievement Division (STAD) can improve students’ reading comprehension in analytical exposition text.